Redescription of the Jamaican orb-weaving spider Chrysometa pecki Levi, 1986 (Araneae, Tetragnathidae), including the first description of the male - Kallal, Robert J.; Hormiga, Gustavo (Zootaxa, 2016)
The tetragnathid genus Chrysometa Simon, 1894 includes 138 species found in the Americas, ranging from the Caribbean to Chile (World Spider Catalog 2015). This genus was revised by Levi (1986), with more recent publications adding to the genus (Álvarez-Padilla 2007, Nogueira et al. 2011, Simó et al., in press). Following Álvarez-Padilla & Hormiga (2011), Chrysometa is differentially diagnosed from other American tetragnathids based on the male palp with a cymbial ectobasal process, cymbial ectomedian process, and embolic basal process, and a paracymbium articulated with a membrane. The epigynum is flat, with fertilization ducts present. Both sexes have guanine crystals in their abdomen and femora lacking trichobothria. Three Jamaican Chrysometa are known: C. pecki Levi, 1986, C. fuscolimbata (Archer, 1958) and C. linguiformis (Franganillo, 1930); all of them known from females only (Levi 1986).